GREEN SPACES AND MENTAL HEALTH: DOES FREQUENCY OF USE OR PROXIMITY AFFECT SUBJECTIVE WELLBEING AND PERCEIVED STRESS? - Hofmann, Maria; Javed, Maryam (PEOPLE: International Journal of Social Sciences, 2019)
Urbanization is essential for economic growth; however, it has a negative effect on the environment and the psychological health of the population. Urban green spaces help in the reduction of air and noise pollution while increasing people’s wellbeing through social interactions and creating an outdoor space for physical activity. Due to the rapid urbanization of the United Arab Emirates, the research on green spaces in this region is fundamental. The study included two hypotheses: 1) Greater proximity and frequency of use results in lower perceived stress and 2) Greater proximity and frequency of use leads to greater wellbeing. The results yielded non-significant for proximity to green spaces and stress and wellbeing. However, frequency of use showed a significant correlation. Additionally, the researchers explored the most common uses of green spaces and suggestions that would increase the frequency of use through open-ended questions. The results could be a manifestation of the Attention Restoration Theory and Biophilia Theory.